Magnetic Silica Nanosystems With NIR-Responsive and Redox Reaction Capacity for Drug Delivery and Tumor Therapy - Jia, Chengzheng; Wu, Hang; Luo, Keyi; Hao, Weiju; Wang, Shige; Huang, Mingxian (Frontiers in Chemistry, 2020)
In recent years, more and more researches have focused on tumor photothermal therapy and chemodynamic therapy. In this study, we prepared a multi-functional nanomaterial with potential applications in the above area. The Fe3O4 nanoparticles were synthesized with suitable size and uniformity, and then coated with mesoporous silica and polydopamine. The unique core-shell structure not only improves the drug loading of the magnetic nanomaterials, but also produces high photothermal conversion efficiency. Furthermore, the reducibility of polydopamine was found to be able to reduce Fe3+ to Fe2+, and thus promote the production of hydroxyl radicals that can kill the tumor cells based on the Fenton reaction. The magnetic nanomaterials are capable of simultaneously combining photothermal and chemodynamic therapy, and permit the efficient treatment for tumors in the future.